2020
DOI: 10.3389/fimmu.2020.01915
|View full text |Cite
|
Sign up to set email alerts
|

To Remember or to Forget: The Role of Good and Bad Memories in Adoptive T Cell Therapy for Tumors

Abstract: The generation of immunological memory is a hallmark of adaptive immunity by which the immune system "remembers" a previous encounter with an antigen expressed by pathogens, tumors, or normal tissues; and, upon secondary encounters, mounts faster and more effective recall responses. The establishment of T cell memory is influenced by both cell-intrinsic and cell-extrinsic factors, including genetic, epigenetic and environmental triggers. Our current knowledge of the mechanisms involved in memory T cell differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 195 publications
(218 reference statements)
1
7
0
Order By: Relevance
“… 35 , 36 The suppressive environment may extend to nearby organs and prevail over a period of time. 37 , 38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 35 , 36 The suppressive environment may extend to nearby organs and prevail over a period of time. 37 , 38 …”
Section: Discussionmentioning
confidence: 99%
“…35,36 The suppressive environment may extend to nearby organs and prevail over a period of time. 37,38 Associations of hepatobiliary cancers with small intestinal and pancreatic cancers do not seem to be explainable by known environmental risk factors. For small intestinal cancer, high unidirectional associations were observed with gallbladder and biliary tract cancers but also with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…This is particular important as there is increasing evidence that the presence of bystander T cells in the tumor microenvironment may play an important role in mediating cellular immune responses against tumor [34][35][36]. The concept of cooperation with the adoptive immune cells (whether specific or bystander cells) with endogenous antigen-specific cytotoxic cells that turn the tumor microenvironment to a controlled tumor growth microenvironment is probably more realistic, particular in the era of immune checkpoint blockade therapy [37]. Many have suggested that the bystander killing of CD8+ T cells is driven by the cytokine stimulation in conjunction with NK surface receptor-mediated killing.…”
Section: Plos Onementioning
confidence: 99%
“…The use of individual fractions of donor immune cells (primarily lymphocytes) for the adoptive therapy of solid cancers is considered. However, the authors express doubts about the duration of the therapeutic effects of adoptive immunotherapy [95]. It is possible that adoptive immunotherapy will find its place in combined regimens for the treatment of solid tumors, along with targeted drugs.…”
Section: Cellular and Immunotherapy Of Breast Cancermentioning
confidence: 99%